Investigation of the Eigenfrequency of the Bending Vibration of the Beam Clamped at Both Ends Around the Principle Directions of Inertia Based on a Single-Degree Freedom Model and a Finite Element Method Analysis - Vadai, Zsolt; Hajdu, Sándor; Kovács, Imre (International Journal of Engineering and Management Sciences, 2021)
In this study, we have dealt with the calculation methods of the eigenfrequencies associated with the bending vibrations of rectangular-shaped beams clamped at both ends. Said eigenfrequencies were determined analytically in the single-degree of freedom model of the beam and the case of the three-dimensional solid and three-dimensional rod models by finite element modal vibration analysis. We presented the calculation method of the characteristics of the analytical model and then calculated the eigenfrequency for a concrete example. We have described the concept of modal characteristics, and in the following, we have determined its natural frequency based on the solid-beam and rod models of the former beam. We calculated and compared the solutions belonging to the models recorded in different ways in 11 additional cases of the presented methods.